Philosophy and the Metaphorical Interpretation of Religious Texts in Averroes, Maimonides, and Aquinas. - Romero Carrasquillo, Francisco J. (Muslim World, 2019)
Scholars specializing in the philosophy of religion are typically well aware that many classical philosophical claims regarding the nature of God tend to be at least I prima facie i divergent from the type of claims regarding God that is usually found in sacred religious texts. My thesis is that whereas it is relatively easy to see how Averroes and Maimonides' views on the interpretation of Scripture are coherent with their own philosophical thought, in the case of Aquinas there is an apparent inconsistency whose solution lies in his understanding of the "literal sense" of Scripture. Aquinas's unique synthesis of faith and reason seeks to uphold both the truth of Scripture and that of natural theology, each on its own grounds without subordinating Scripture to philosophy or disparaging philosophy in favor of Scripture. See also M. Aillet, I Lire la Bible avec s. Thomas: Le passage de la "littera" a la "res" dans la Somme théologique i , Studia Friburgensia 80, Fribourg: Éditions Universitaires, 1993; C. Berchtold, I Manifestatio Veritatis: Zum Offenbarungsbegriff bei Thomas von Aquin i , Dogma und Geschichte 1, Münster: Lit, 2000; J.F. Boyle, "St. Thomas Aquinas and Sacred Scripture", I Pro Ecclesia i 4 (1995), 92-104; L.J. Elders, "Aquinas on Holy Scripture as the Medium of Divine Revelation", in I La doctrine de la revelation divine de saint Thomas d'Aquin i , Studi Tomistici 32 (Vatican City: Libreria Editrice Vaticana, 1990), 132-152; E. Menard, I La Tradition, Révélation, Écriture et Église selon saint Thomas d'Aquin i , Studia 18, Bruges: Desclée, 1964; B. Decker, "Schriftprinzip und Ergänzungstradition in der Theologie des hl.